EVALUATION OF THE COVID-19 SURVEILLANCE SYSTEM IN POLTAVA OBLAST DURING THE WAR IN UKRAINE - Berezhna, Antonina; Chumachenko, Tetyana (Eastern Ukrainian Medical Journal, 2024)
The objective of the study was to evaluate the surveillance system for COVID-19 in Poltava Oblast during the war in Ukraine. Materials and methods. The bibliosemantic method was used and a retrospective epidemiological analysis of official data on morbidity, mortality and lethality from COVID-19 in Poltava Oblast for the years 2020–2022 was carried out. According to the methodology of the Centers for Disease Control and Prevention, USA, the simplicity, flexibility, acceptability, timeliness and representativeness of the surveillance system were evaluated, its suitability and resource consumption were determined. Results. The incidence of COVID-19 in Poltava Oblast in 2020–2022 among adults was higher than among children with a peak incidence among adults of 8,121 cases per 100,000 adult population in 2021, among children 2,980 cases per 100,000 child population in 2022. The highest rates of mortality and lethality from COVID-19 in Poltava Oblast were registered in 2021. The health care system for COVID-19 in Ukraine is represented at the local, regional and national levels. In Poltava Oblast, epidemiological surveillance is carried out at the local level by health care institutions, at the regional level by the Disease Control and Prevention Centers of the Ministry of Health of Ukraine. The complexity of the surveillance system is determined by several levels of reporting, the need for special laboratory tests to confirm the case, the need to collect epidemiological data during the investigation of cases, additional training of personnel on working with the modules of the Electronic Integrated Disease Surveillance System (EIDSS). The surveillance system will remain effective in the post-pandemic period, and can be adapted for other infectious diseases. It is possible to reduce the flexibility of the surveillance system when applying electronic document flow and timeliness due to the delay in the collection, transmission and analysis of epidemiological data due to the destruction of the energy infrastructure during the war. The acceptability of the surveillance system is positively influenced by the presence of a regulatory framework, but attitude depends on the commitment of medical workers to the implementation of new technologies and their personal and professional characters. The surveillance system for COVID-19 is representative only for severe and moderate cases of the disease. During the war, the sensitivity of the surveillance system for COVID-19 in Ukraine may be poor due to the difficult access to medical care in the occupied, de-occupied and front-line territories. A large amount of human and material resources is required for the uninterrupted operation of the surveillance system. Conclusions. The surveillance system for COVID-19 in Poltava Oblast is conducted by person, place, time. The evaluated surveillance system is complex and multi-level. In the conditions of war, the sensitivity, flexibility and timeliness of the surveillance system may reduced. There is a need to increase the training of specialists in epidemiology and public health and to find additional sources of funding for the surveillance network institutions, since the surveillance system for COVID-19 is resource-intensive.